Relationship between shoulder abduction strength and rotator cuff tear in elderly women: a general population study - Andrew J Carr; Nigel K Arden; Hannah Hinsley; Charlotte Ganderton (BMJ Open, 2023)
Objectives To investigate the effect of age-related rotator cuff tears on shoulder strength in a general population cohort.Design Cross sectional observational study.Setting This study was set in an outpatient clinic setting in Chingford, North East London, and was a component of the 20 year visit of the Chingford 1000 women cohort.Participants Individuals were part of the Chingford 1000 women cohort, a 20-year-old longitudinal population study. This cohort has been extensively characterised as representative of the population of the UK. At the 20 year visit, 446 attended for shoulder assessment and were aged between 64 and 87.Primary and secondary outcome measures Isometric shoulder abduction strength measured using a Nottingham Mecmesin Myometer and the presence of rotator cuff pathology, determined via ultrasound examination (GE voluson i portable ultrasound machine with a 10-16MHz linear probe). Shoulders were classified into normal, abnormal tendon/partial tear, full-thickness tears (>0 and ≤2.5 cm) and full-thickness tears (>2.5 cm). Symptoms were defined using the Oxford Shoulder Score, where an abnormal score was defined as symptomatic.Results 446 women (891 shoulders) aged 71 (range 65–84) were included in the study. Age, the presence of pain and the non-dominant arm were demonstrated to reduce strength. Rotator cuff tears and pathology had no isolated effect on shoulder strength in those aged under 70. However, in the over 70s full-thickness tears>0 and ≤2.5 cm, and >2.5 cm had mean reductions of 6.3 and 12.7 N, respectively (p<0.001).Conclusion Rotator cuff tears of all sizes in those aged under 70 were not associated with a loss of shoulder strength. In those aged over 70, strength was reduced by 30% with small and 40% with large full thickness tears. Loss in strength was associated a loss of ability to perform activities of daily living but only for large tears.